2015
DOI: 10.7710/2162-3309.1210
|View full text |Cite
|
Sign up to set email alerts
|

University Faculty Awareness and Attitudes towards Open Access Publishing and the Institutional Repository: A Case Study

Abstract: INTRODUCTIONThe purpose of this study was to understand TAMU faculty awareness of open access (OA) publishing; assess their attitudes towards, and willingness to, contribute to an institutional repository (IR); and investigate their perceptions of newer OA trends and resources, including Open Educational Resources (OER) and DMPTool. The survey also served as an outreach tool to inform and educate TAMU faculty about OA publishing, the IR, and the Libraries' OA services. METHODS The 34-question survey was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 23 publications
(26 reference statements)
8
85
0
2
Order By: Relevance
“…It was also found that senior researchers were more likely to offer open access to their publications than junior researchers (Lwoga & Questier, 2015). The Texas A&M University has had an institutional open access policy since 2013, and despite its short existence, the degree of awareness of the policy and the institutional repository among professors and researchers is high (Yang and Li, 2015). However, the biggest difficulty found by its researchers was how to deposit documents, followed by concerns about copyright issues and the feeling that the contents of the repository were of lower quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that senior researchers were more likely to offer open access to their publications than junior researchers (Lwoga & Questier, 2015). The Texas A&M University has had an institutional open access policy since 2013, and despite its short existence, the degree of awareness of the policy and the institutional repository among professors and researchers is high (Yang and Li, 2015). However, the biggest difficulty found by its researchers was how to deposit documents, followed by concerns about copyright issues and the feeling that the contents of the repository were of lower quality.…”
Section: Introductionmentioning
confidence: 99%
“…The respondents most often found the policy on the website of the journal or publisher and, if they were unable to find it, they asked for permission to add their documents to the repository. Continuing in order of frequency, the researchers used the library services or (Creaser et al, 2010;Frass, Cross, & Gardner, 2014;Kim, 2011;Yang & Li, 2015). Many of the respondents have now changed from an attitude of concern to one of actively seeking editorial policies, which means that they have found a motivation for depositing their documents in the institutional repository.…”
Section: Analysis By Subject Areamentioning
confidence: 99%
“…Of particular relevance to this paper, the authors assert that "it is likely that, for the short term at the very least, green and gold OA models will continue to complement each other" (Rowley et al, 2017(Rowley et al, , p. 1209. Yang and Li's (2015) study of Texas A&M University faculty attitudes toward OA and institutional repositories found strong awareness of OA, along with concerns regarding mandates and scholarly quality. Much of their work confirmed previous studies on barriers to repository participation, which included concerns over quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, the scholarly reward system continues to mean that academics trade their copyright to publish in their preferred journals, which has thus far been seen as more advantageous to them compared with any benefits they could gain from retaining their copyright [26,32,40]. It has been shown that many academics believe that publishing in traditional journals is most likely to contribute to promotions and pay rises, rather than making their work available in an OA form [41][42][43].…”
Section: Copyright and Culturementioning
confidence: 99%